Penggunaan Zoom Breakout Rooms dalam Penerapan Metode Cooperative pada Pelajaran Vocabluary - Rusydi Muhammad Yusuf (SAP (Susunan Artikel Pendidikan), 2021)
The corona virus has spread in the world, because of this situation, the teaching and learning process has also changed, from face to face learning process to a learning process carried out via video conference. Zoom with breakout rooms is one of the most widely used types of video conference in the teaching and learning process. In this study, zoom with breakout rooms was used to examine the application of the cooperative method in vocabulary building lesson. For this purpose, students who were involved in the teaching and learning process were divided into small groups to discuss with each other. The process was that after all 30 students were in the main room, they were divided into 6 groups where each group consists of 5 students. After that they were given the opportunity to discuss for 20 minutes to understand the material being studied. The research was held in Darma Persada University at even semester 2020-2021. The method used was qualitative. The result of this study was that the use of zoom with breakout rooms can be used as an alternative in applying cooperative learning method where the students were in small group consisting of 5 students in one group.